Investigation of the relationship between electrodermal and behavioural responses to executive tasks in Prader-Willi syndrome: An event-related experiment. (February 2019) - Chevalère, J.; Jauregi, J.; Copet, P.; Laurier, V.; Thuilleaux, D.; Postal, V.
Highlights: A slight impairment of inhibition and a severe impairment of working memory updating in Prader-Willi syndrome. Abnormalities in the sympathetic autonomic nervous system in Prader-Willi syndrome. Specific sympathetic autonomic signatures in Prader-Willi syndrome. Distinct sympathetic responses to different cognitive processes in all participants . Independence of autonomic dysfunctions and executive impairments in Prader-Willi syndrome. Abstract: Background: Recent work suggests that maladaptive behaviors in genetic developmental disorders may emerge from autonomic dysfunctions impacting higher order executive functions. In Prader-Willi syndrome (PWS), executive functions are not well understood and investigations of possible underlying causes at the autonomic level are lacking. Aims: This study aimed at clarifying the status of inhibition and working memory updating functions in PWS and searched for sympathetic signatures as well as to examine their links with executive performance. Methods and Procedures: The performance of thirty adults with PWS was compared to that of thirty healthy adults on two tasks assessing inhibition and working memory updating while electrodermal activity (EDA) was recorded. Outcomes and Results: PWS adults underperformed healthy adults in the inhibition and the working memory updating tasks and showed abnormal skin conductance responses. Distinct EDA have been found in PWS and healthy adults. Furthermore, while EDA reflected distinct cognitive processes, correlations between electrodermal and behavioural data were absent when examining the two groups separately. Conclusions and Implications: PWS is associated with a slight impairment of inhibition and a severe impairment of working memory updating. Furthermore, there are specific sympathetic autonomic signatures in PWS that do not present straightforward links with executive dysfunctions.